Experiences of students with visual impairments in adoption of digital talking textbooks: an interpretative phenomenological analysis - Hussin, Ahamad, author; Folkestad, James E., advisor; Makela, Carole J., committee member; Timpson, William M., committee member; Johnson, Thomas E., committee member (Colorado State University. Libraries, 2013)
Assistive technology devices have become essential tools for students with visual impairments. In 2009, the Malaysian Ministry of Education introduced Digital Talking Textbooks (DTTs) for selected subjects to facilitate learning. The purpose of this qualitative study was to explore, describe, and interpret the experiences of students with visual impairments in using DTTs to assist their learning. The study looked at what factors influence students with visual impairments to adopt or to reject DTTs. Data were obtained from 12 students' in-depth interviews. Tentative themes emerged, were refined, and became the six emergent super-ordinate themes for this research: (1) functionality of the innovation, (2) support to use the innovation, (3) knowledge of the innovation, (4) challenges for effective use of the innovation, (5) alternatives to the innovation, and (6) adaptation of the innovation. Providing in-house training for teachers and students, affordable tools, and sufficient trial and usage time for students are recommended to ensure DTTs are efficiently adopted.
Keywords: digital talking textbook; students with visual impairments; special education